When Teachers Become Parents: Parenthood Influence on Greek Teachers’ Professional Lives - Koutrouba, Konstantina; Eirini Kalantzak; Ioannis Christopoulos (European Journal of Social Science Education and Research, 2017)
The present study examines 30 Greek teachers’ views about changes that took place after they became parents regarding teaching and learning, communication and cooperation with students and parents, and attitudes towards teacher profession. The data were collected through semi-structured face to face in-depth interviews, based on 25 close- and open-ended questions, and classified into categories using content analysis. The research indicates, inter alia, that parenthood had a major impact on teachers’ empathy, on attitudes towards low-achievers, and on the implemented teaching procedures per se. It also shows that teachers who became parents tend to improve their communication with their students’ parents, to be more tolerant of criticism, and to be more patient and supportive as regards students’ academic and socio-affective achievements. Regarding at-home planning and preparation, and physical, mental and emotional fatigue of teachers during parenthood, the present study reveals developing burning-out symptoms, which are, however, counterbalanced by strong feelings of rewarding love and acceptance displayed by their students. It finally shows that parenthood does not subjugate the professional aspirations of vivid, ambitious teachers, although female teachers who became parents are expected to face more obstacles than their male colleagues during their professional and family life, especially if they hold a position in school administration, lack the provision of at-home help or have family children who display learning or other physical disabilities or misbehavior problems.
Keywords: teachers; parenthood; changes; education; Greece